Impact of G6PD deficiency on liver damage and disease progression in hepatocellular carcinoma: a cross-sectional study in Thailand - Jugnam-Ang, Watcharapong; Tansakul, Phatchayanat; Chanda, Makamas; Cheepsunthorn, Poonlarp; Tangkijvanich, Pisit; L. Cheepsunthorn, Chalisa (Chulalongkorn Medical Journal, 2025)
Background: Glucose 6-phosphate dehydrogenase (G6PD) is a key enzyme involved in the pentose phosphate pathway that produces reduced nicotinamide adenine dinucleotide phosphate to support redox homeostasis and cancer cell proliferation. While G6PD deficiency has been linked to reduced cancer risk, its influence on hepatocellular carcinoma (HCC) remains unclear. Objectives: This study aimed to investigate the prevalence of G6PD deficiency in patients with HCC and its association with clinical parameters across the disease stages. Methods:A cross-sectional study analyzed G6PD activity and clinical data from 174 patients with HCC, 100 patients infected with the hepatitis B virus (HBV), and 154 healthy controls. Peripheral blood G6PD activity was measured, and the clinical parameters were compared between patients with early- and advanced-stage HCC with and without G6PD deficiency. Results: The prevalence of G6PD deficiency was comparable across patients with HCC (6.9%), patients with HBV infection (6.0%), and healthy controls (6.5%) (P = 0.97), with no notable difference in clinical parameters between early- (6.7%) and advanced-stage HCC (7.0%). Median G6PD activity was significantly higher in patients with HCC (7.9 ± 2.1 U/g Hb) compared to healthy controls (7.1 ± 2.5 U/g Hb) (P < 0.05). Patients with advanced-stage HCC exhibited elevated G6PD activity (8.1 ± 2.5 U/g Hb), largely because of anemia. The patients with G6PD deficiency and HCC, particularly at the advanced stage, had elevated liver damage markers, including alkaline phosphatase (125.0 ± 68.8 U/L), serum glutamic-oxaloacetic transaminase (69.5 ± 78.0 U/L), and alpha-fetoprotein (258.8 ± 1,010.1 ng/mL) levels. Conclusion: G6PD deficiency does not appear to reduce HCC susceptibility but is associated with increased liver damage in patients with HCC at an advanced stage. These findings highlight the potential importance of G6PD in the progression of liver cancer and the need for further research regarding its therapeutic implications.